Dissociation of E-cadherin/β-catenin complex by MG132 and bortezomib enhances CDDP induced cell death in oral cancer SCC-25 cells. Issue 8 (December 2015) - Lü, Lanhai; Liu, Xiqiang; Wang, Cheng; Hu, Fengchun; Wang, Jianning; Huang, Hongzhang
Highlights MG132 or bortezomib inhibited cell proliferation and induced cell death in oral cancer SCC-25 cells. MG132 or bortezomib plus CDDP led to synergistic effects on SCC-25 cells. MG132 or bortezomib damaged E-cadherin/β-catenin complex during cell apoptosis. The use of MG132 or bortezomib with CDDP could reverse CDDP resistance in oral cancer.